DEVELOPMENT OF DIGESTIVE ENZYMES ACTIVITY ON BLACK SADDLED CORAL GROUPER (Plectropomus laevis) LARVAE - Bejo Slamet; Titiek Aslianti (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2016)
ABSTRACTProtease, amylase, and lipase enzymes were used as biological indicators to measure larvae’s food digestion. The aim of this study was to describe digestive enzyme activity development of black saddled coral grouper (Plectropomus laevis) larvae. The just hatching larvae were reared in concrete tank 2x3x1 m3 with stocking density of 10 larvae/L. In the larval rearing media were added with Nanochloropsis oculata at 105 cel/ml started from 1 day old (D-1). The larvae was fed with rotifer (Brachionus rotundiformis) at 10-20 ind/ml started from D-2 and artificial diet from D-10. To analyze  the protease, amylase, and lipase enzymes activities, samples were taken 0.5-1 g or about 1000 larvae on D-3, D-4, D-6, D-8 and 500 larvae on D-10, D-12, D-16, and D-20. The result showed that the protease, amylase, and lipase enzymes activity were positively correlated with the growth. Digestive enzymes activity was increased when larvae started on endogenous feeding (D-3), become down on D-6, stable on D-8 to D-10, increased on D-12, and reached the highest level on D-16. Digestive enzymes activity was higher when larvae started feeding with artificial diet compared to the larvae before feeding with artificial diet. Keywords:  digestive enzymes, development, larvae, blacksaddled coral grouper